Dual‐Permeability Model Improvements for Representation of Preferential Flow in Fractured Clays. Issue 8 (21st August 2020) - Aguilar‐López, Juan P.; Bogaard, Thom; Gerke, Horst H.
Abstract: Dual‐permeability models assume that the complete porous media system can be represented by two different interacting subsystems: the matrix and the fracture pore domain. For some soils like fractured clays, the fracture domain may be empty, which makes its physical behavior differ significantly from capillary flow. Our main hypothesis is that this kind of preferential flow systems can be represented as a dual‐permeability porous media by adapting the 2‐D formulation and initial conditions of the fracture domain and the mass exchange function. The performance of the dual‐permeability finite element solution was evaluated by comparing it to its equivalent 2‐D explicit fracture single‐permeability finite element model. The results of the numerical experiments show that the 2‐D dual‐permeability concept allows to simulate preferential flow in soils with fractures. This was achieved by improving the parameterization of the Mualem‐van Genuchten soil water retention curve of the fractured domain and the hydraulic conductivity exchange function for the first‐order mass exchange term for fractured soils. The exchange term hydraulic conductivity evaluated at the minimum value of the pressure heads of the two domains considerably improved the results as compared to using the well‐established arithmetic average of the hydraulic conductivity values from both domains. These two improvements of the dual‐permeability model approach are especially useful in cases where preferential flow systems consist mostly of relatively large, noncapillary fractures and macropores. Key Points: Dual‐permeability model improvement for modeling wide fractures by reformulating the α parameter in the Mualem‐van Genuchten model soil water retention curve (SWRC) Rigorous evaluation of the dual‐permeability interface mass exchange function SWRC exponent n sensitivity analysis for dual‐permeability model